Pemberdayaan UMKM Desa Nangewer Melalui Model Pasar Mingguan Partisipatif Untuk Kemandirian Ekonomi Lokal - Rhiswandi, Rhandi; Yus Djunaedi Rusli; Dedeh Kurniasih; Marsya Elianwar; Salsabillah Agustiawati (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: The community service program in Nangewer Village, Darangdan District, Purwakarta Regency, aims to empower local MSME actors and strengthen the village's economic independence post-pandemic through the development of a participatory weekly market model. This activity involved 25 MSME actors, village officials, and Youth Organizations in planning, training, and implementing weekly markets combined with social activities such as mass gymnastics, local culinary, and children's games. The results of the evaluation showed an increase in the daily income of business actors from IDR 6.23 million to IDR 11.52 million, or an increase of 85%, with income stability of 40%. In addition to having an economic impact, this activity increases social interaction across hamlets and strengthens the role of women in household businesses. The main obstacles in the form of limited facilities and waste management are overcome through synergy with BUMDes and the support of the Village Fund. This activity shows good practices of collaboration between the community, village government, and universities in developing sustainable micromarkets, which can be replicated as a model of economic empowerment in other villages. Keywords: MSME; Community Empowerment; Weekly Market; Village Economy Abstrak: Program pengabdian masyarakat di Desa Nangewer, Kecamatan Darangdan, Kabupaten Purwakarta, bertujuan memberdayakan pelaku UMKM lokal dan memperkuat kemandirian ekonomi desa pasca-pandemi melalui pengembangan model pasar mingguan partisipatif. Kegiatan ini melibatkan 25 pelaku UMKM, perangkat desa, dan Karang Taruna dalam perencanaan, pelatihan, dan pelaksanaan pasar mingguan yang dikombinasikan dengan kegiatan sosial seperti senam massal, kuliner lokal, dan permainan anak. Hasil evaluasi menunjukkan peningkatan pendapatan harian pelaku usaha dari Rp6,23 juta menjadi Rp11,52 juta, atau naik 85%, dengan stabilitas pendapatan 40%. Selain memberikan dampak ekonomi, kegiatan ini meningkatkan interaksi sosial lintas dusun dan memperkuat peran perempuan dalam usaha rumah tangga. Hambatan utama berupa keterbatasan fasilitas dan pengelolaan sampah diatasi melalui sinergi dengan BUMDes dan dukungan Dana Desa. Kegiatan ini menunjukkan praktik baik kolaborasi antara masyarakat, pemerintah desa, dan perguruan tinggi dalam mengembangkan pasar mikro yang berkelanjutan, yang dapat direplikasi sebagai model pemberdayaan ekonomi di desa lain. Kata kunci: UMKM; Pemberdayaan Masyarakat; Pasar Mingguan; Ekonomi Desa